054 Plaque vulnerability is an important feature of chronic stable coronary disease: a comparison of lesion characteristics in stable angina and acute coronary syndrome patients using virtual histology. (22nd September 2015) - Murray, SW; Stables, RH; Hart, G; Perry, RA; Palmer, ND
Abstract : Introduction: Rupture of a vulnerable plaque is the most important mechanism leading to acute coronary syndromes (ACS). Studies have shown that the most common feature of these plaques is the presence of a thin-cap fibroatheroma (TCFA). Previous studies have also shown the presence of TCFA and healed plaque rupture in some stable lesions. We sought to compare directly the frequency of TCFA and volume of necrotic core present in stable angina (SA) patients, referred for PCI, to those from patients presenting with high-risk ACS. Intravascular Ultrasound (IVUS) derived Virtual Histology (VH) was used to determine plaque morphology as it is validated against post-mortem histological findings. Methods: This single centre, prospective, observational study received ethical approval locally. 15 SA and 45 ACS patients (CD=30; NCD=15) were recruited. IVUS-VH imaging was undertaken using a phased array catheter (EagleEye catheter, 2.9 F/20 MHz; Volcano Corp) with a continuous motorised pullback of 0.5 mm/s. Plaque composition and analysis was determined by off-line analysis (PC VIAS 3.0.394 software; Volcano Corporation) From post-mortem correlation data, the highest risk VH-Thin Cap Fibroatheroma (TCFA) consists of three or more IVUS-VH frames with a confluent necrotic core greater than 20% and no evidence of a fibrous cap. Each lesion pullback was examined frame by frame for VH-TCFA and the overall mean percentage of necrotic core present in each lesion type was calculated. An unpaired t-test was used to compare normally distributed data. Results: Sixty lesions and 3543 IVUS-VH frames were analysed in total (15 SA/30 CD/15 NCD) We found no statistical differences between SA and NCD plaque volume constituents (mm 3 ): Fibrous=51.4±33.6 vs 66.7±48.7 p=0.32; Fibrofatty=8.7±6.3 vs 12.5±11.9 p=0.3; Necrotic Core=22.5±15.8 vs 29.3±40.1 p=0.5 and Dense Calcium=13.8±11.8 vs 11.2±14.4 p=0.6) SA lesions had on average 1.86 TCFA per lesion which was very similar to 1.88 TCFA per lesion in unstable CD (p=ns). NCD had a trend towards more TCFA per patient (2.33 vs 1.86, p=0.2). SA lesions typically had a reduced mean total plaque volume (mm 3 ) compared to ACS culprit lesions (SA=162±93 < CD=261±138 p=0.02) and therefore a significantly reduced mean volume (mm 3 ) of all plaque constituents except dense calcium. However, the mean percentage of unstable necrotic core, per lesion type, was not different: SA 22.7% vs CD 21.9% vs NCD 21.3% p=0.75. Conclusions: Stable coronary artery lesions differ from culprit ACS lesions in terms of the quantity of plaque present. However, they do not differ from culprit or non-culprit lesions in the percentage contribution of unstable plaque. Importantly, high risk VH-TCFA appears to occur with similar prevalence across the groups. There are structural similarities between SA and NCD lesions suggesting that some SA lesions that contain increased numbers of TCFA are not benign.